Erodibility Status of Some Soils in Akoko-Edo Local Government Area of Edo State, Nigeria - W.P. Agbai; O.J Tate; I. U. Efenudu (Bulgarian Journal of Soil Science, 2022)
Due to the detrimental effect of water erosion, erosion data must be gathered for sustenance of soil structure and utilization. The aim of the study was to determine the erodibility status of the some soils in Akoko-Edo Local Government Area of Edo state, Nigeria. Soil samples were taken from representative pedons dug from the three communities namely Ikpeshi, Unem-Nekhua and Ososo. The samples were subjected to routine analysis and results were used to calculate the erodibility indices of Clay Dispersion Ration (CDR), Clay Disperion Index (CDI), Clay Flocculation Index (CFI) and Bouyoucous Erodibility Index (EIROM). The data derived were subjected to statistical analysis, to determine mean separation at 5% probability, coefficient of variation and standard error. The results showed that the soils were dominated by the sand fraction, mainly sandy loam with clay increment down the horizons becoming loamy sand and sandy clay loam. Soil pH ranged from an average of 5.36 – 5.62 across the pedons. Electrical Conductivity (EC) mean across the pedons ranged from 23.88 µS/cm (0.02388 dS/m) - 36.11 µS/cm (0.0361 dS/m) which posed no salinity threat. Organic matter was low with average of 9.28 – 14.85 g/kg across the pedons. Across the horizons, the CDR ranged from 53.7 - 62.3%, CDI (42.5 - 59.2%), CFI (34.52 - 43.1%) and EIROM (1.92 - 3.93). Clay had highly significant negative correlation (r= -0.7235) with CDI and EIROM (r = -0.9730). Sand had positive correlation with CDI (r = 0.7597) and EIROM (r = 0.9130). CDR also had a positive correlation (r = 0.8306) with CDI. CDI had a positive correlation (r = 0.6945) with EIROM. Variation for all index was low, ranging from 0.1-3. The result shows that the soils are erodible and sustainable and conservational agriculture practice should be carried out.